(untitled) (Fiep Bulletin - online, 2016)
The purpose of this paper is to present the correlation between levels of physical fitness and body image of swimming paraatletas. The research was qualitative and quantitative nature, associated with the descriptive field research with application of a questionnaire. The locus of the investigation was the Industry Social Service - SESI, Maracanaú, Ceará. We had to sample seven athletes who met the inclusion criteria. To collect data we used two instruments: Disorder Questionnaire Body Dysmorphic and aerobic endurance test in the water. The results showed that the aerobic endurance capacity of the group split with 42% excellent, 29% good and 29% fair featuring a good cardiorespiratory fitness even though the test is not adapted for people with disabilities all reached an acceptable standard related fitness the non-disabled people of the same gender and age. The results regarding the questionnaire Disorder Dismófico Body, proved that disabled athletes involved in competitive swimming, with experience of local and regional competitions and a training routine has a self-perception of their positive body, so its deficiency in the environment training for it becomes unnoticeable, because it is able to improve their full potential, achieve their physical independence and social respect for evidence of resilience and achievements, a fact that goes beyond this environment and improves your social life. Thus, we come to conclusion that the correlation between the level of physical fitness of the group of athletes and body image was positive, and the performance gained with the potentiating factor practice good self esteem and increased positive self-perceived body image.